Carbon Balance in a Batch Biochemical Reactor - Betancur , Rodrigo A. (My University, 1970)
Measurement of cellular carbon has been accomplished by gravimetric, titrimetric or directly measuring CO₂ produced in the combustion of organic carbon in the Carbon Analyzer Gravimetric and titrimetric methods are cumbersome, inaccurate at concentrations higher than 600mg/l.
The purpose of this series of experiments is to find an alternative method for measuring cellular carbon. The proposed method is based in a carbon balance in which the soluble and gaseous forms of carbon are monitored. Cellular carbon is calculated by subtracting the sum of the soluble and gaseous forms of carbon from the initial total carbon found in the reactor.
Keywords: measurement of cellular carbon; combustion